Hydrothermal Synthesis and Electrochemical Characterization of Hexagonal Zr-CuS Nanocomposite and its Charge Storage Capacity - Brown, J. William; Geetha, D.; Ramesh, P.S.; Podili, Surekha (Asian Journal of Chemistry, 2020)
Hexagonal zirconia doped CuS nanaocomposites were successfully synthesized through a simple mild hydrothermal synthesis. The higher dopent concentration of zirconia produces increased mesoporous homogeneous nanostructures. The structure and nature of the resulting product (Zr-CuS) were characterized by XRD, XPS, SEM/EDS and TEM techniques. The results show that zirconia is homogeneously dispersed on CuS and well separated from one another. Electrochemical studies show that the final product (Zr-CuS) possesses high specific surface area. An increase in zirconia concentration might increase the mesopore volume and a widening of microporosity. Zirconia doped CuS composite exhibits high electrochemical performance with a high capacitance of 949.47 F g-1. The presence of zirconia in CuS improves the capacitive behaviour of samples. Therefore, Zr-CuS could be promising nanocomposite for energy storage device.